1999
DOI: 10.1097/00002030-199905070-00006
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of antiretroviral combination therapy on activation, apoptosis and regeneration of T cells in HIV-1-infected children and adolescents

Abstract: Different mechanisms may contribute to early T cell reconstitution in HIV-1-infected children and adolescents during ART: decreased activation-induced apoptosis leading to increased survival of circulating primed/memory T cells; decreased activation-induced naive-to-memory shift increasing the frequency of circulating resting/naive T cells; increased input of haematopoietic progenitor cells from the bone marrow into the thymus and decreased intrathymic T cell death leading to an increased thymic output of naiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 28 publications
3
47
1
1
Order By: Relevance
“…One possibility is HIV-1 protease that is well known to cleave host cell proteins and transfected HIV-1 protease kill host cells (67). HIV-1 protease inhibitor-based therapy to treat AIDS inhibits apoptosis (68). HIV-1 protease inhibitors have had little impact on HAD because they have limited penetration across the blood-brain FIGURE 11.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is HIV-1 protease that is well known to cleave host cell proteins and transfected HIV-1 protease kill host cells (67). HIV-1 protease inhibitor-based therapy to treat AIDS inhibits apoptosis (68). HIV-1 protease inhibitors have had little impact on HAD because they have limited penetration across the blood-brain FIGURE 11.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the susceptibility of peripheral blood T cells to apoptosis decreased in HIV-1 infected adults and children under HAART [41,42]. However, whether such a phenomenon reflects the direct down-regulation of Tlymphocyte apoptosis by PIs or is merely the consequence of normalized T-lymphocyte function (such as increased proliferation to recall antigens, decreased plasma cytokines, declined serum b2-microglobulin and other soluble activation markers) [2,4,28] remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…55 Importantly, the magnitude of CD4 þ T-cell apoptosis observed in HIV-infected individuals correlates well with the stage of HIV disease. [56][57][58][59][60][61] In addition, changes in the levels of T-cell apoptosis after highly active antiretroviral therapy (HAART) predict the immunological response (i.e., increase in CD4 T-cell count), thus confirming the link between disease progression and apoptosis. [62][63][64] Taken together, these observations indicate that the increased susceptibility to apoptosis of T lymphocytes from HIV-infected individuals is a marker of HIV disease progression and support the hypothesis that the chronic immune system activation that Figure 2 Overview of apoptosis pathway.…”
Section: T-cell Apoptosis and Aidsmentioning
confidence: 92%